Analysis of the Role of Marketing Mix and Brand Equity on Customer Satisfaction Dining Places - Hendy Tannady; Yohanes Totok Suyoto; Magdalena (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of brand equity and marketing mix on consumer satisfaction Demie Bakmie (Como Park). This study uses a quantitative method with purposive sampling, namely consumers who have visited Demie Bakmie (Como Park) as many as 175 respondents. The results showed that brand equity has an effect on consumer satisfaction and the marketing mix has an effect on consumer satisfaction. In addition, both brand equity and the marketing mix jointly influence consumer satisfaction.